Conceptual Study of Shodhana and Shamana Chikitsa - Awasthi, Sakshi; Gandharve, Satish; Sood, Rajesh; Sharma, Sonia (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda’s primary goal is to prevent and cure various diseases. Concept of Chikitsa (Treatment) in Ayurveda has been extensively well defined, divided into three main aspects on Shodhana (Purification Therapy), Shamana(Pacification Therapy) and Nidana Parivarjana(Avoiding causative factors). Panchakarma therapy of Ayurveda has caught the attention of people all over the world since it is a unique type of treatment for various chronic, auto immunological, hormonal, and degenerative problems, among others, where other types of treatments have failed. Acharya Charaka emphasized the importance of Panchakarma therapy by noting that the ailment healed by Shodhana will never recur, however the disease treated by Shamana therapy may resurface in the future. Here, in this article an attempt has been made to analyse the concept of Shodhana and Shamana Chikitsa as mentioned in classical texts of Ayurveda.